2022
DOI: 10.1111/jace.18595
|View full text |Cite
|
Sign up to set email alerts
|

Cold sintering co‐firing of (Ca,Bi)(Mo,V)O4–PTFE composites in a single step

Abstract: Because of large differences in the processing temperature windows between ceramics and polymers, the single-step co-sintering of microwave dielectric ceramic-polymer substrates remains challenging. In this work, a dense (Ca 0.65 Bi 0.35 )(Mo 0.65 V 0.35 )O 4 (CBMVO) ceramic was first prepared through cold sintering at 150 • C, under a uniaxial pressure of 300 MPa for 60 min with Li 2 MoO 4 (LMO) as a transient low-temperature solvent. Cold-sintered CBMVO-5 wt% LMO ceramic shows excellent microwave dielectric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…28 Due to the ultralow sintering temperature, CSP is feasible to fabricate multi-material systems, such as ceramic-polymer, ceramic-2D material, and ceramicmetal composites. [29][30][31][32][33][34][35][36] Moreover, the low sintering temperature and short holding time can effectively inhibit the exaggerated grain growth, indicating that CSP has great application potential in the preparation of nanome-ter or submicron functional ceramics. At present, CSP has successfully applied in microwave dielectric, ferroelectric, piezoelectric, target material, lithium battery, thermoelectric, and optical material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Due to the ultralow sintering temperature, CSP is feasible to fabricate multi-material systems, such as ceramic-polymer, ceramic-2D material, and ceramicmetal composites. [29][30][31][32][33][34][35][36] Moreover, the low sintering temperature and short holding time can effectively inhibit the exaggerated grain growth, indicating that CSP has great application potential in the preparation of nanome-ter or submicron functional ceramics. At present, CSP has successfully applied in microwave dielectric, ferroelectric, piezoelectric, target material, lithium battery, thermoelectric, and optical material.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other sintering methods, it dramatically reduces the energy consumption, which is only 1/10–1/100 of that for TTS process 28 . Due to the ultralow sintering temperature, CSP is feasible to fabricate multi‐material systems, such as ceramic–polymer, ceramic‐2D material, and ceramic–metal composites 29–36 . Moreover, the low sintering temperature and short holding time can effectively inhibit the exaggerated grain growth, indicating that CSP has great application potential in the preparation of nanometer or submicron functional ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…A range of works have demonstrated that novel phases and materials, such as polymers (thermoplastics and thermosets), 15–20 2D materials, 21,22 and buckminsterfullerene, 23 can all be readily incorporated into the grain boundaries of a sintered ceramic material. Previously, a number of examples have been made of the cold sintering of low‐loss dielectrics with other fillers 24,25,26–35 .…”
Section: Introductionmentioning
confidence: 99%
“…Provided there is one phase that is the major volume fraction in the composite (the matrix) that can undergo sintering, other phases (the filler) can be integrated into the body and from the composite. [9][10][11][12][13][14] A range of works have demonstrated that novel phases and materials, such as polymers (thermoplastics and thermosets), [15][16][17][18][19][20] 2D materials, 21,22 and buckminsterfullerene, 23 can all be readily incorporated into the grain boundaries of a sintered ceramic material. Previously, a number of examples have been made of the cold sintering of low-loss dielectrics with other fillers.…”
Section: Introductionmentioning
confidence: 99%